EVALUATION OF THE SANDNESS OF THE NGRAYONG LAYER IN THE XYZ WELL OF PERTAMINA ASSET IV CEPU - Edi Untoro; Kristofol Waas (Asosiasi Dosen Muda Indonesia, 2024)
Most oil and gas wells produce through sandstone formations deposited in marine or detrital environments. Marine sedimentary sands, in which most of the hydrocarbons are found, are often cemented with calcareous or siliceous minerals and may be heavily consolidated. In contrast, Miocene and younger sands are often unconsolidated or only partially consolidated with soft clays or silts. This formation, which is structurally weak, is unlikely to be able to withstand the movement of sand grains. When oils are produced at high flow rates, they can produce sands along with the liquid oil. The movement of fluid through the sandstone reservoir creates stresses in the sand grains due to differences in fluid pressure, fluid friction, and overburden pressure. If this stress exceeds the formation holding force, then the sand grains and fines can move and can be produced with oil liquid. Rapid changes in the liquid production rate can cause unstable conditions which can result in increased sand production. When an oil well begins to produce water, this will often be an indication of the start of sand production. Muecke[1], demonstrated that particle motion occurs in a multiphase system when the wetting phase begins to move. Even consolidated sandstone can be mechanically and chemically damaged over time as the reservoir is produced. The overburden stress on the sand grains will increase as the reservoir pressure decreases. The movement of water can dissolve the minerals that cement the sand grains and can change the production capacity of the formation fluid. Smooth migration can reduce permeability in the perforations. This can result in higher pressure drops in the wellbore and changes in formation stress. Formations cemented by calcite can be damaged by improperly designed acidification, and can result in increased production of sand.